Ossodas, a portable digital system for seismological signal acquisition (2004)
This paper presents the concept and design of a digital system to record seismological signals. The hardware and software designed has been interfaced to the PC 104 BUS architecture in order to achieve a modular system to acquire, process, record and transmit seismic data by telemetry. The modularity of this system offers independence technology from the manufacturers of this kind of equipments both in hardware and software, also because the system was developed under the Linux operating system GNU, which allows easy update of hardware; the software is an open platform developed in C, which allows the user to configure the system to operate online and updating according to needs.In brief, we propose in this paper a system design option for seismological instrumentation, which presents significant advantages also for other regions and countries with high seismicity and needs of earthquake monitoring, but have serious limitations in acquiring and maintaining commercial systems imported from developed countries.